Computer analysis of images and patterns : 17th International Conference, CAIP 2017, Ystad, Sweden, August 22-24, 2017, Proceedings.: 17th International Conference, CAIP 2017, Ystad, Sweden, August 22-24, 2017, Proceedings. Part II (2017) - Unknown
No abstract available